An annotated bibliography of celebral palsy resources, 2000-2009 - Dacillo, Jimzon E. (2009)
The problem of the scarcity of information about Cerebral Palsy, especially to the families with disabled members, is lingering in the Philippines. Even the basic status or the number of Filipinos afflicted with this disability is not accurate. The government has no concrete program regarding this case.